Impact of electrocardiographic findings for diagnosis of left ventricular hypertrophy in patients with primary aldosteronism. (March 2015) - Kurisu, Satoshi; Iwasaki, Toshitaka; Mitsuba, Naoya; Ishibashi, Ken; Dohi, Yoshihiro; Kihara, Yasuki
Background: Compared to patients with similar levels of hypertension, patients with primary aldosteronism have a greater left ventricular hypertrophy (LVH). The presence of LVH should be detected as early as possible to prevent cardiovascular complications associated with the condition. We evaluated comparative diagnostic value of electrocardiographic (ECG) indexes for LVH in patients with primary aldosteronism. Methods: ECG and echocardiographic data were obtained in 88 patients with primary aldosteronism. We analyzed the four most commonly used ECG indexes, including Sokolow-Lyon index, Cornell voltage index, Cornell product index, and Gubner index. Results: Echocardiographic LVH was found in 35 patients (40%). Sensitivity ranged from 0% for Gubner index to 49% for Cornell product index. Specificity ranged from 81% for Sokolow-Lyon index to 100% for Gubner index. Sokolow-Lyon index ( r =0.43, p <0.001), Cornell voltage index ( r =0.55, p <0.001) and Cornell product index ( r =0.52, p <0.001) correlated significantly with left ventricular mass (LVM) index. No significant correlation was found between Gubner index and LVM index. Conclusions: ECG indexes had a reasonably high specificity, but a low sensitivity for LVH in patients with primary aldosteronism. Cornell voltage index and Cornell product index had a better diagnostic value of LVH, and had a better correlation with LVM index in these patients.